2005
DOI: 10.1080/02652040400026350
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization andin vitrorelease properties of ibuprofen-loaded microspheres based on polylactide, poly(϶-caprolactone) and their copolymers

Abstract: In this paper, ibuprofen was encapsulated into microspheres by oil-in-water (o/w) emulsion solvent evaporation method. Biodegradable polymers with certain compositions and characteristics such as polylactide (PLA), poly(epsilon-caprolactone) (PCL) and their block copolymer were used to prepare the microspheres. The results indicate that, under the same processing conditions, the drug entrapment efficiency was similar (approximately 80%) for microspheres prepared with PLA and P(LA-b-CL) (78.7/21.3 by mole), but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…10). This indicated that shikonin was no longer present as a crystalline material but has been converted into an amorphous state (Yu et al, 2009b) and was uniformly dispersed in the CA matrix (Zhu et al, 2005). PLLA indicated an endothermic peak at 190 • C corresponding to its melting point.…”
Section: Thermal Analysismentioning
confidence: 96%
“…10). This indicated that shikonin was no longer present as a crystalline material but has been converted into an amorphous state (Yu et al, 2009b) and was uniformly dispersed in the CA matrix (Zhu et al, 2005). PLLA indicated an endothermic peak at 190 • C corresponding to its melting point.…”
Section: Thermal Analysismentioning
confidence: 96%
“…However, these systems have tended to produce initial burst release of drug, and control of the level of drug loading can be difficult (Bodmeier & Chen, 1989;Flandroy, Grandfils, & Jerome, 1993;Jain, 2000;Oh, Nam, Lee, & Park, 1999;Zhu et al, 2005). In these delivery systems, the rate of release tends to be controlled by the level of drug loading, as well as a combination of the aqueous solubility and molecular weight of the drug, system morphology, and, to a lesser extent, the rate of polymer degradation (Fu, Shyu, Su, & Yu, 2002;Perumal, Dangor, Alcock, Hurbans, & Moopanar, 1999;Tice & Cowsar, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…4c). For microspheres, it was also reported the rougher surface area and numerous interconnecting networks of semicrystalline polymers while amorphous polymers showed smoother surface areas [26]. Moreover, PCL blend with P(DL)LA was reported to have less interconnecting network, smoother surface areas and denser polymer matrix than PCL homopolymers [27].…”
Section: Sem Analysismentioning
confidence: 96%